2014
DOI: 10.1534/g3.114.010546
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Regulatory Network Coordinating Cell Cycles DuringC. elegansDevelopment Is Revealed by a Genome-Wide RNAi Screen

Abstract: The development and homeostasis of multicellular animals requires precise coordination of cell division and differentiation. We performed a genome-wide RNA interference screen in Caenorhabditis elegans to reveal the components of a regulatory network that promotes developmentally programmed cell-cycle quiescence. The 107 identified genes are predicted to constitute regulatory networks that are conserved among higher animals because almost half of the genes are represented by clear human orthologs. Using a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
3
7
0
Order By: Relevance
“…On the other hand, Clone Mapper identified 23 new targets with of score >1, 9 of which had a score >50 ( Supporting Information , Table S1 ). Similar results were obtained for the two other studies ( Fievet et al 2013 ; Roy et al 2014 ) ( Table 1 , Table S2 , and Table S3 ). In all cases, the novel targets identified with Clone Mapper formed part of a closely linked network ( Figure 6 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, Clone Mapper identified 23 new targets with of score >1, 9 of which had a score >50 ( Supporting Information , Table S1 ). Similar results were obtained for the two other studies ( Fievet et al 2013 ; Roy et al 2014 ) ( Table 1 , Table S2 , and Table S3 ). In all cases, the novel targets identified with Clone Mapper formed part of a closely linked network ( Figure 6 ).…”
Section: Resultssupporting
confidence: 89%
“…A list of novel targets identified with Clone Mapper for the RNAi clones used by Fievet et al was used as input to GeneMania (yellow circles), together with the genes corresponding to the 14 mutant strains used in the study (black circles). (C) Roy et al performed a screen to find components of a regulatory network that promotes developmentally programmed cell-cycle quiescence ( Roy et al 2014 ). Novel targets identified with Clone Mapper for the RNAi clones used by Roy et al (yellow), together with common targets (black) were used as input to GeneMania.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the physiological activity that promotes the rapid responses we observed, we monitored calcium levels in freely behaving animals using the genetically encoded indicator GCaMP3.0 [ 47 ]. Our behavioral assays indicated that egl-1 mutants, lacking the HSN serotonergic neuron type [ 48 , 49 ], were indistinguishable from wild-type (data not shown). Therefore, to study cellular mechanisms, we focused on the physiological activity in NSM and ADF prior to, during, and after re-feeding encounters.…”
Section: Resultsmentioning
confidence: 99%
“…However, this form limited its utility and may have led to some confusion when searching for worm genes with human orthologs, as evidenced by publications that referenced OL1, but missed genes that were in the spreadsheet and thus reported a lower degree of reliability for this list (e.g. Roy et al 2014). To facilitate access, we subsequently developed a basic online tool, which was never formally published but instead publicized through a reader comment at the original journal Web site and announcements in C. elegans venues.…”
Section: The Legacy Gene Setmentioning
confidence: 99%